LEGENDA SUMUR SONGO DESA SIDOKUMPUL, KECAMATAN GRESIK, KABUPATEN GRESIK (ANALISIS STRUKTUR NARATIF, NILAI BUDAYA, DAN RESEPSI MASYARAKAT) - Miftahul Huda; Syahruliya Romadloni Wahidah; Megi Widiyah Utami (Pendidikan Bahasa dan Sastra Indonesia, 2021)
This study aims to describe the oral literature in the Gresik area, namely the legend of the songo well. This study uses a descriptive qualitative method with the object of oral literature in the form of a legend. The background of this research is the village of Sidokumpul Gresik. The data collection techniques used, observation techniques, interview techniques, recording techniques, recording techniques, and transcription techniques. The results of this study are, (1) the narrative structure includes plot, term, function, and actors of the Legend of the Songo Sumur. (2) cultural values ​​obtained from this study are values ​​related to fellow human beings, and (3) community reception is the belief believed by the people of Sidokumpul village about the legend of the Songo Sumur, so that the legend is used as a historical relic.